2019
DOI: 10.1007/s40264-019-00857-8
|View full text |Cite
|
Sign up to set email alerts
|

Benefit-Risk Assessment of Alogliptin for the Treatment of Type 2 Diabetes Mellitus

Abstract: The dipeptidyl peptidase-4 inhibitor (DPP-4i) alogliptin is an oral, antidiabetic treatment that is approved in many countries to treat patients with type 2 diabetes mellitus (T2DM), including the USA, Europe, and Japan. Alogliptin is efficacious both as monotherapy and as add-on/combination therapy with other commonly prescribed T2DM treatments, such as metformin and pioglitazone. Overall, alogliptin is well-tolerated in patients with T2DM, including older patients, those with renal and/or hepatic impairment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 134 publications
(311 reference statements)
0
14
0
1
Order By: Relevance
“…Insurance claims databases have been increasingly used for studies to identify risk factors for cardiovascular disease and to compare the effectiveness of drugs in treating cardiovascular disease 6‐8 . Recently, studies using claims data have increased in the field of diabetes in Japan 9‐17 . In Japan claims data are recorded electronically using unique master codes 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Insurance claims databases have been increasingly used for studies to identify risk factors for cardiovascular disease and to compare the effectiveness of drugs in treating cardiovascular disease 6‐8 . Recently, studies using claims data have increased in the field of diabetes in Japan 9‐17 . In Japan claims data are recorded electronically using unique master codes 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The safety and tolerability of vildagliptin and allogetine were good 24,25 . They have potential as first‐line treatments for patients with T2DM in Asia 26 . There is no increase in cardiovascular risk from the current evidence 27,28 .…”
Section: Discussionmentioning
confidence: 94%
“…24,25 They have potential as first-line treatments for patients with T2DM in Asia. 26 There is no increase in cardiovascular risk from the current evidence. 27,28 Liraglutide is a representative GLP-1 receptor agonist, and a large number of studies have confirmed its beneficial hypoglycemic effects and good safety profile.…”
Section: Clinical Trials Of Diabetes Drugsmentioning
confidence: 90%
“…However, in the last decade the DPP-4 inhibitors, so called gliptins were developed. Gliptins exert antihyperglycemic effect and are used for treatment of diabetes Type 2 [61]. Another agent used in prevention of Type 2 diabetes is a rare, naturally existing sugar, 3-C epimer of fructose, Dallulose (D-psicose).…”
Section: Gut Processes Hypothalamic Signals About Hungermentioning
confidence: 99%